Evaluation of Lumbar Spine Load by Computational Method in Order to Acknowledge Low-back Disorders as Occupational Diseases - Hlávková, Jana; Lebeda, Tomáš; Tichý, Tomáš; Gaďourek, Petr; Urban, Pavel; Nakládalová, Marie; Laštovková, Andrea; Fenclová, Zdenka; Ridzoň, Petr; Ehler, Edvard; Richter, Milan; Pešáková, Lenka; et al. (My University, 2016)
Aim: The aim of the study was to develop a computational module for the prediction of compressive force on the L4/L5 disc suitable for use in field settings. Method: The value of compressive force is intended to be used as a proxy measure of the mechanical burden of low-back when performing work activities. The compressive force predicted by the module in a particular worker should be compared with the NIOSH limit value of 3,400 N for the assessment of lumbar spine load during manual lifting tasks. Exceeding the limit will be considered as the fulfilment of “hygienic criterion” that should be met to acknowledge low-back disorder as an occupational disease. To develop the computational module we used the ergonomic software TECNOMATIX Classic Jack taking into account the anthropometric parameters of a worker and ergonomic parameters of his/her work activity. Results: We calculated compressive forces on the L4/L5 disc in about 1,300 simulated combinations of various factors influencing compressive force. Parameters which turned out to be crucial for the compression of L4/L5 disc were included in the computational algorithm. Conclusion: Our study was primarily aimed at the assessment of lumbar disorders as occupational diseases. Moreover, the study can contribute to the recommendation of preventive measures to decrease health risks in occupations associated with the overload of low-back region. The graphic maps generated by the computational module enable a fast and exact analysis of particular job.
Hodnocení přetížení bederní páteře počítačem zpracovanou metodou za účelem přiznání poruchy bederní páteře jako nemoci z povolání.
Keywords: low-back disorders; low-back pain; compressive force; manual lifting; lumbar spine load assessment; biomechanical analysis; ergonomic software; trunk posture; evaluation; prediction; time; frequency; criteria; prevention; poruchy bederní páteře; bolesti bederní páteře; kompresivní síla; manuální úkony; zhodnocení zátěže bederní páteře; biomechanická analýza; egonomický software; postavení těla; zhodnocení; progóza; čas; frekvence; kritéria; prevence